Analysis Of The Influence Of The Marketing Mix And Word Of Mouth On Parents' Decisions To Choose Educational Services (Case Study Of SD Muhammadiyah Binjai Hulu, Sintang Regency) - Adlim Dwi Fatmoko; Yasir Hudzaifah; Zainur Ikhsan (UNIVED Press, 2025)
Education is a structured journey designed to enhance awareness and transform the attitudes and behaviors of individuals or groups Education serves as the cornerstone for the ongoing journey of life. It plays a significant part in forming people and is essential to the improvement of society, the country, and the state as a entirety . The point of this consider is to evaluate how much the showcasing blend and word of mouth affect parents' choices with respect to instructive administrations at SD Muhammadiyah Binjai Hulu The strategy utilized for the investigate is quantitative . The research utilizes primary data collected through questionnaires.The participants in this research are the parents of students at SD Muhammadiyah Binjai Hulu, amounting to 100 respondents. The strategy of examination utilized is different straight relapse . The factors in this investigate incorporate free factors, particularly the promoting blend and word of mouth, beside the subordinate variable, which is the choice made by guardians with respect to the determination of instructive administrations at SD Muhammadiyah Binjai Hulu . The discoveries demonstrate that both the promoting blend and word of mouth emphatically and essentially impact parents' choices at the same time . Partial testing indicates that the marketing mix significantly affects parental decisions, with a computed t-value of 3.027 compared to a t-table value of 1.984.